Efforts to increase interest in learning Arabic and psychological well-being at the Sanggar Bimbingan Muhammadiyah (SBM) Kepong Malaysia - Ahmad Zaki Annafiri; Hardi Santosa; A. Syahid Robbani; Qaem Aulassyahied; Fitria Sari Yunianti; Muhammad Shollahuddin; Rahmat Sabili; Ahmad Mizaj El Kafoor (Universitas Muhammadiyah Magelang, 2023)
The focus of this community service is the Sanggar Bimbingan Muhammadiyah (SBM) in Kepong, Malaysia, where Arabic subjects are currently unavailable. Additionally, SBM Kepong faces challenges related to teaching staff who lack knowledge about effective learning methods. In response to these issues, this community service aims to stimulate an interest in learning Arabic based on Al-Islam and Muhammadiyah principles, as well as enhance the psychological well-being of teachers at the Muhammadiyah Kepong Guidance Studio through the development of innovative learning methods. The steps involved include: 1) field assessment, 2) preparation of materials, 3) counseling, and 4) evaluation. The outcomes of this program reveal that 3 out of 4 participants experienced increased knowledge, and overall satisfaction with the activity implementation was quite high.